Canfod y ffordd: Noddfa, Symbolaeth, a’r Iaith Gymraeg: Storïau Menywod sy’n Ailsefydlu yng Nghymru | Navigating Sanctuary, Symbolism, and the Welsh Language: The Stories of Women Resettling in Cymru/Wales - SARAH TIERNEY (2024)
Against hostile rhetoric and policymaking, the Welsh Government set out to become the world’s first Nation of Sanctuary. This interdisciplinary thesis draws on participatory research insights to respond to the Nation of Sanctuary declaration. It maps out the resettlement realities of 17 sanctuary-seeking women based in urban South-East and urban and rural North Cymru/Wales, including the views of 3 of their Support Workers. This thesis considers the women’s stories through the prism of language and identity. However, ranging (and intersecting) geopolitical and social factors govern the realities of forced migration and resettlement, particularly in a devolved, minority language context such as Cymru/Wales. This intricate reality necessitates a comparably intricate analysis. Hence, the thesis is best understood as four interconnected narratives, which each make up, affect, and alter the fabric of Welsh resettlement. The first narrative is supranational forced migration management and governance. Critically, global histories of forced migration protection, and connections between initial developments with present-day EU, UK, and Welsh approaches to resettlement. The second narrative explores the multi-national level and analyses the securitisation of displacement in public discourse and policymaking, with the 2015 European border control response, Brexit, and Hostile Environment rhetoric used to exemplify this claim. The third narrative takes a national perspective, and looks inward at Cymru/Wales, analysing the concept of Welshness and the Welsh language, including historical accounts of Welsh language peripheralisation. Influenced significantly by current minority language debate, but also the participant’s stories, this narrative presents Welshness from a de-territorialised perspective, challenging ascriptions which bind place to certain people and to specific languages. The final narrative connects the thesis debate, drawing on theories of symbolic power and the state to explore sanctuary-seeking experiences in Cymru/Wales, raising queries regarding the symbolic potential of minority languages to facilitate and contribute to sanctuary provisions (Bourdieu, 1991). Utilising this conceptual framework and chronology, including the participants’ stories, this thesis finds resettlement in Cymru/Wales, for some but not all participants, to be characterised by immigration and asylum hostility, not least securitisation. However, it further finds a unique (and underutilised) symbolic entity which enables sanctuary seeking women, in some instances, to mobilise capital and facilitate connection to their resettlement context. Namely, the Welsh language. While influenced significantly by Sociolinguistics, particularly regarding the participatory and consultative research approach adopted for data collection, this thesis takes an unbounded approach to theory and practice. It draws on concepts associated with Geography, International Relations, History, among others, to provide a comprehensive analysis and overview of resettlement. This interdisciplinary approach enables a greater understanding of how governance, past and present, not least national, multinational and supranational, affects the everyday lives and stories of people forced to flee their homes. Importantly, however, it further highlights the complexity of Welsh resettlement, its influences, insights, and oversights, providing a framework for future investigations of Cymru/Wales, its Sanctuary pledge, and the role of the Welsh language in future sanctuary provisions. In so doing, this thesis demonstrates the potential of Cymru/Wales to move beyond providing symbolic sanctuary, hinting at potential approaches to restorative, welcoming futures in Welsh resettlement (Edwards and Wisthaler, 2023).